2009
DOI: 10.1055/s-0029-1233234
|View full text |Cite
|
Sign up to set email alerts
|

Lernen ohne Ende. Die medizinische Leitlinie – ein Weiterbildungsinstrument mit Zukunft?

Abstract: Ein langer Arbeitstag in Ihrer internistischen Praxis geht zu Ende. Glücl Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…Evidence-based medical guidelines seem to be helpful in this respect, but often effectiveness of guidelines is low due to insufficient dissemination and implementation [1-4]. Studies have shown a small but positive influence of continuing medical education (CME), continuing professional development (CPD), and knowledge transfer/translation (KT) on physicians' knowledge, attitudes, skills, and competences [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence-based medical guidelines seem to be helpful in this respect, but often effectiveness of guidelines is low due to insufficient dissemination and implementation [1-4]. Studies have shown a small but positive influence of continuing medical education (CME), continuing professional development (CPD), and knowledge transfer/translation (KT) on physicians' knowledge, attitudes, skills, and competences [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Narrative Reviews stellen dagegen umfassend ein Krankheitsbild hinsichtlich Diagnostik und Therapie dar [2][3][4]. Diese Informationsflut umfasst mehr als 20 000 biomedizinische Zeitschriften jährlich und weltweit mehr als eine Million wissenschaftliche Artikel und verdoppelt sich etwa alle 10 Jahre [5]. Der Dschungel der medizinischen Literatur ist heutzutage praktisch nicht mehr zu durchdringen [6].…”
Section: Einleitung ▼unclassified
“…This flood of information comprises more than 20,000 biomedical journals per year with worldwide more than 1 million of scientific articles and nearly doubles every 10 years [5]. It is actually no longer possible to manage this jungle of medical literature [6].…”
Section: Introductionmentioning
confidence: 99%